A Discrete Choice Approach to Modeling Food Store Access. (April 2015) - Hillier, Amy; Smith, Tony; Cannuscio, Carolyn C; Karpyn, Allison; Glanz, Karen
Assessments of access to healthful food frequently use GIS to measure the distance and concentration of food outlets relative to where residents live. These descriptive approaches do not account for food shopping behavior, which may vary based on the attributes of food shoppers and their activity space—places where they live, work, access resources, and socialize. Building on transportation research about accessibility, we reframe the issue of food access and equity from one about 'what is nearby?' to 'where do people shop?'. We use a conditional logit model to analyze disaggregate data from a door-to-door survey of food shopping choice and food store surveys conducted in a predominantly non-Hispanic Black and middle-income and low-income section of Philadelphia. Our results highlight the importance of distance from home to food stores, overall, but they also emphasize the influence on food store choice of the race and sex of food shoppers, travel mode, and where they spend time other than at home, as well as food prices and the availability of healthful foods. This approach to understanding food access holds promise for future research that can link store choice to specific food purchases and health outcomes as well as for refining place-based strategies for improving access to healthful foods.